Pengaruh PKH dan BPNT terhadap Kemiskinan dengan Pertumbuhan Ekonomi Sebagai Variabel Moderasi - Lilik Rodhiatun Nadhifah; Nur Huri Mustofa (Prodi Perbankan Syariah FAI UMT, 2021)
This research is motivated by the number of poverty in Pucakwangi which is still quite high and deserves to receive Social Assistance. The purpose of this study was to determine the effect of the Family Hope Program (PKH), and the Non-Cash Assistance Program on poverty in Pucakwangi District with economic growth as a moderating variable. This research is a quantitative research with secondary data from related institutions such as BPS, Social Service, and Social Assistance Institutions. The data used is Time series data from 2018-2020. The population of this study is the entire Pucakwangi community receiving the Social Assistance Program for PKH and BPNT from 20 villages. By taking samples by means of purposive sampling from 20 audited villages multiplied quarterly to get a sample of 80. The analytical tool used is Eviews. The results showed that the Family Hope Program had a significant negative effect on poverty. The non-cash assistance program has a negative and significant effect on poverty. The hopeful family program which moderated economic growth had no significant negative effect. The Non-Cash Food Assistance Program moderated by economic growth has an insignificant negative effect.